Pelestarian Nilai Dan Simbol Islam-Jawa Dalam Ruang Keagamaan Masjid Menara Kudus Perspektif Pierre Bourdieu - Muhammad Rizky Shorfana; Ahmad Muhctar Luthfi (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
The Menara Kudus Mosque is a historical site that represents the acculturation of Javanese and Islamic culture through its architecture, symbols, and religious practices within it. This study aims to examine the preservation of Islamic-Javanese values and symbols embodied in the religious space of the Menara Kudus Mosque through the perspective of Pierre Bourdieu. The research employs a qualitative method with an ethnographic approach, utilizing observation, in-depth interviews, and literature study. The findings reveal that the Menara Kudus Mosque is not merely a place of worship, but also a socially meaningful space, where the transmission of Islamic-Javanese values takes place through collective rituals, historical narratives, and everyday practices that are repetitive yet symbolically charged. The cultural and symbolic capital contained in elements such as the temple-like tower, the khoul tradition, the prohibition of slaughtering cows, and the pilgrimage to the tomb of Sunan Kudus, demonstrates a form of legitimized power that is socially institutionalized and culturally inherited. In this context, the mosque functions as a field of value preservation, where Islam is not presented in an exclusive form but is intertwined with local structures of meaning that have been internalized within the community’s habitus. This study recommends that local religious spaces be reflectively read as living social texts, which not only preserve tradition but also shape religious consciousness and cultural identity in ways that remain relevant in addressing contemporary challenges.